Coating diaphragm for lithium ion battery as well as preparation method and application of coating diaphragm
By improving the spraying process and controlling key process parameters, a lithium-ion battery separator with higher consistency and stability was prepared, which solved the problem of high thermal shrinkage rate of the separator and inconsistent density of the spraying surface at high temperatures, and improved the energy density and cycle life of the battery.
Patent Information
- Application Number
- CN202510142351.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-03-28
AI Technical Summary
The existing lithium-ion battery separators have high thermal shrinkage at high temperatures, which easily break holes and lead to short circuits in the battery. The sprayed diaphragm has poor density consistency, unstable adhesive force, and large fluctuations in the height and size of the glue point.
By improving the spraying process, the slurry solid content, coating speed, nozzle diameter, feed flow rate and turntable rotation speed are controlled to produce coated diaphragm with higher consistency and stability.
It improves the overall hardness of the diaphragm, facilitates the battery cell to enter the shell, enhances the energy density and cycle life of the battery, and increases the discharge rate.
Smart Images

Figure BDA0005265287940000081 
Figure BDA0005265287940000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery diaphragms, and more specifically, to a coated diaphragm for lithium ion batteries and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used as power sources for various mobile devices due to their high energy density, high operating voltage, no memory effect and long cycle life. However, frequent lithium-ion battery safety accidents have attracted people's attention. Lithium-ion batteries usually include positive electrodes, negative electrodes, separators and electrolytes. As a barrier between the positive and negative electrodes, the separator plays a vital role in the performance of lithium-ion batteries. Therefore, research on improving the safety, usability and processability of lithium-ion batteries by improving the performance of the separator has received more and more attention.
[0003] Polyolefin separators (polyethylene PE, polypropylene PP) are the most widely used lithium-ion battery separators at present, but they have the problem of too high thermal shrinkage rate, softening and deformation at above 100°C, and the melting point is lower than 170°C. When the battery temperature rises due to internal or external factors, the separator will shrink or melt and then rupture, causing the positive and negative poles of the battery to contact and cause the battery to short-circuit, causing accidents such as battery combustion and explosion. In order to improve the thermal stability of polyolefin separators, the current main solution is to coat one or both sides of the polyolefin separator. During the battery charging and discharging process, even if the polyolefin film shrinks or even melts, the coating can still maintain the integrity of the separator, which can effectively prevent the positive and negative large area short circuit. At the same time, it can also effectively improve the surface tension of the separator, reduce the interface impedance between the separator and the pole piece, and improve the liquid absorption performance of the separator. There are currently two commonly used coating materials for diaphragm coatings. One is inorganic coatings, such as alumina, boehmite, silica and other ceramic coatings, which can effectively improve the high-temperature resistance of the diaphragm. However, the ceramic coating has poor bonding with the base membrane and is prone to powdering problems. The addition of binders will cause the diaphragm's air permeability to deteriorate, and the strong water absorption of ceramics will cause the battery performance to deteriorate. The other is PVDF coating, which can effectively improve the adhesion between the diaphragm and the electrode, but has limited improvement in the diaphragm's high-temperature resistance.
[0004] The current spray diaphragm glue coating surface density consistency is poor, the adhesion is unstable, the glue point height fluctuates greatly, and the glue point size D50 fluctuates greatly. Summary of the invention
[0005] The invention provides a coated diaphragm for lithium ion batteries, a preparation method and an application thereof, and improves the problems of poor consistency of surface density, unstable adhesion, large fluctuation of glue point height and large fluctuation of glue point size D50 of the current sprayed diaphragm by improving the spraying process.
[0006] In a first aspect, the present invention provides a method for preparing a coated separator for a lithium ion battery, comprising the following steps:
[0007] (1) Slurry preparation: PVDF spray slurry preparation, the slurry solid content is 6-15%;
[0008] (2) Feeding: The slurry is circulated on the machine, passes through a nozzle with a diameter of 0.8-1.5 mm, and is dispersed and atomized under a turntable with a diameter of 110 mm and 360 teeth. The feed flow rate is 3000-5000 mL / min and the turntable speed is 5000-10000 rpm;
[0009] (3) Unwinding: Load the base film onto the coating machine, start the coating machine, and operate it at a coating speed of 60-150 m / min;
[0010] (4) Spraying: The sprayer gate is opened and the atomized slurry is sprayed onto the surface of the base film;
[0011] (5) Drying: The coated film is dried in an oven;
[0012] (6) Winding: Use a winding mechanism to roll the dried coating film onto a winding core to obtain a finished coating film.
[0013] Preferably, in step (1), the PVDF spray slurry comprises the following raw materials by mass: 300 to 600 parts of deionized water, 0.04 to 0.25 parts of pH buffer regulator, 85 to 99.5 parts of vinylidene fluoride monomer, 0.5 to 15 parts of comonomer, 0.5 to 3 parts of sodium carboxymethyl cellulose, 0.2 to 6 parts of nano-hydroxyapatite powder, 0.3 to 3 parts of metallocene synergist, 0.2 to 1.0 parts of initiator and 0.08 to 0.35 parts of dispersant.
[0014] Preferably, in step (1), the PVDF spray slurry comprises the following raw materials by mass: 400 to 600 parts of deionized water, 0.08 to 0.25 parts of pH buffer regulator, 90 to 99.5 parts of vinylidene fluoride monomer, 2.5 to 15 parts of comonomer, 1.5 to 3 parts of sodium carboxymethyl cellulose, 0.5 to 6 parts of nano-hydroxyapatite powder, 0.8 to 3 parts of metallocene synergist, 0.2 to 1.0 parts of initiator and 0.08 to 0.35 parts of dispersant.
[0015] Preferably, in step (1), the PVDF spray slurry comprises the following raw materials by mass: 500 parts of deionized water, 0.20 parts of pH buffer regulator, 95 parts of vinylidene fluoride monomer, 12 parts of comonomer, 2.5 parts of sodium carboxymethyl cellulose, 3.2 parts of nano-hydroxyapatite powder, 2.8 parts of metallocene enhancer, 1.0 parts of initiator and 0.25 parts of dispersant.
[0016] Preferably, the dispersant is one or more of polypropylene ammonium salts, fatty acid polyethylene glycol esters, guar gum, and fatty acid polyethylene glycol esters.
[0017] Preferably, the initiator is one or more of benzoyl peroxide, tert-butyl peroxide, dialkyl peroxide and dihydrogen peroxide.
[0018] Preferably, the method for preparing the PVDF spray slurry comprises the following steps:
[0019] S1: Mix deionized water, pH buffer regulator, vinylidene fluoride monomer, comonomer and sodium carboxymethyl cellulose under a pressure of 5.5-8.0 MPa and a temperature of 40-65° C. to obtain a mixture A;
[0020] S2: adding nano-hydroxyapatite powder and metallocene enhancer to mixture A, mixing and stirring uniformly to obtain mixture B;
[0021] S3: adding an initiator and a dispersant to the mixture B, mixing, stirring and dispersing, and preparing a PVDF spray slurry.
[0022] Preferably, in step (4), the base film comprises a commercial PP single-layer film, a PE single-layer film or a PP and PE multi-layer composite base film.
[0023] Preferably, in step (5), the drying temperature is 45-60°C.
[0024] In a second aspect, the present invention provides a coated diaphragm for a lithium ion battery, which is prepared by the method for preparing a coated diaphragm for a lithium ion battery.
[0025] In a third aspect, the present invention provides a coated separator for a lithium ion battery and its application in a lithium ion battery.
[0026] In summary, the present invention has the following beneficial effects:
[0027] 1. The present invention manufactures a coated diaphragm for lithium-ion batteries by controlling five parameters: slurry solid content, coating speed, nozzle diameter, feed flow rate, and turntable speed;
[0028] 2. The coated diaphragm for lithium-ion batteries prepared by the present invention can improve the problems of poor consistency of the diaphragm coating surface density, unstable adhesion, large fluctuation of the glue point height, and large fluctuation of the glue point size D50, thereby improving the overall hardness of the battery core, facilitating the battery core to be placed in the shell, improving the battery energy density, increasing the battery cycle life, and increasing the discharge rate;
[0029] 3. The coated diaphragm for lithium-ion batteries prepared by the present invention is applied to lithium-ion batteries to improve the overall hardness of the battery core, facilitate the insertion of the battery core into the shell, increase the battery energy density, and increase the battery cycle life.
[0030] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present invention. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the reactions are carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0032] Preparation Example
[0033] Preparation Example 1
[0034] A PVDF spray slurry comprises the following raw materials by weight: 300 parts of deionized water, 0.04 parts of a pH buffer regulator, 85 parts of a vinylidene fluoride monomer, 0.5 parts of a comonomer, 0.5 parts of sodium carboxymethyl cellulose, 0.2 parts of a nano-hydroxyapatite powder, 0.3 parts of a metallocene synergist, 0.2 parts of an initiator and 0.08 parts of a dispersant; the dispersant is a polypropylene ammonium salt; the initiator is benzoyl peroxide;
[0035] The preparation method of PVDF spray slurry comprises the following steps:
[0036] S1: Mix deionized water, pH buffer regulator, vinylidene fluoride monomer, comonomer and sodium carboxymethyl cellulose under a pressure of 5.5 MPa and a temperature of 40° C. to obtain a mixture A;
[0037] S2: adding nano-hydroxyapatite powder and metallocene enhancer to mixture A, mixing and stirring uniformly to obtain mixture B;
[0038] S3: adding an initiator and a dispersant to the mixture B, mixing, stirring and dispersing, and preparing a PVDF spray slurry.
[0039] Preparation Example 2
[0040] A PVDF spray slurry comprises the following raw materials by weight: 500 parts of deionized water, 0.20 parts of a pH buffer regulator, 90 parts of a vinylidene fluoride monomer, 12 parts of a comonomer, 2.5 parts of sodium carboxymethyl cellulose, 3.2 parts of nano-hydroxyapatite powder, 2.8 parts of a metallocene synergist, 0.5 parts of an initiator and 0.25 parts of a dispersant; the dispersant is a polypropylene ammonium salt; the initiator is benzoyl peroxide;
[0041] The preparation method of PVDF spray slurry comprises the following steps:
[0042] S1: Mix deionized water, pH buffer regulator, vinylidene fluoride monomer, comonomer and sodium carboxymethyl cellulose under a pressure of 6.0 MPa and a temperature of 65° C. to obtain a mixture A;
[0043] S2: adding nano-hydroxyapatite powder and metallocene enhancer to mixture A, mixing and stirring uniformly to obtain mixture B;
[0044] S3: adding an initiator and a dispersant to the mixture B, mixing, stirring and dispersing, and preparing a PVDF spray slurry.
[0045] Preparation Example 3
[0046] A PVDF spray slurry comprises the following raw materials by weight: 600 parts of deionized water, 0.25 parts of a pH buffer regulator, 99.5 parts of a vinylidene fluoride monomer, 15 parts of a comonomer, 3 parts of sodium carboxymethyl cellulose, 6 parts of nano-hydroxyapatite powder, 3 parts of a metallocene synergist, 1.0 parts of an initiator and 0.35 parts of a dispersant; the dispersant is a polypropylene ammonium salt; the initiator is benzoyl peroxide;
[0047] The preparation method of PVDF spray slurry comprises the following steps:
[0048] S1: Mix deionized water, pH buffer regulator, vinylidene fluoride monomer, comonomer and sodium carboxymethyl cellulose under a pressure of 8.0 MPa and a temperature of 65° C. to obtain a mixture A;
[0049] S2: adding nano-hydroxyapatite powder and metallocene enhancer to mixture A, mixing and stirring uniformly to obtain mixture B;
[0050] S3: adding an initiator and a dispersant to the mixture B, mixing, stirring and dispersing, and preparing a PVDF spray slurry.
[0051] Example
[0052] Example 1
[0053] A method for preparing a coated diaphragm for a lithium ion battery comprises the following steps:
[0054] 1. Slurry preparation: Prepare the PVDF spray slurry prepared in Example 1, the solid content of the slurry is 15%;
[0055] 2. Feeding: The slurry circulates on the machine, passes through a nozzle with a diameter of 0.8 mm, and is dispersed and atomized under a turntable with a diameter of 110 mm and 360 teeth. The feed flow rate is 3000 ml / min and the turntable speed is 5000 RPM.
[0056] 3. Unwinding: Load the base film onto the coating machine, start the coating machine, and run it at a speed of 60m / min;
[0057] 4. Spraying: The sprayer gate is opened, and the atomized slurry is sprayed onto the surface of the base film;
[0058] 5. Drying: The coating film is dried in an oven;
[0059] 6. Rewinding: Use the rewinding mechanism to receive the dried coating film onto the reel core to obtain the finished coating film.
[0060] Example 2
[0061] A method for preparing a coated diaphragm for a lithium ion battery comprises the following steps:
[0062] 1. Slurry preparation: Prepare the PVDF spray slurry prepared in Example 2, the solid content of the slurry being 15%;
[0063] 2. Feeding: The slurry circulates on the machine, passes through a nozzle with a diameter of 1.0 mm, and is dispersed and atomized under a turntable with a diameter of 100 mm and 360 teeth. The feed flow rate is 4000 ml / min and the turntable speed is 6000 RPM.
[0064] 3. Unwinding: Load the base film onto the coating machine, start the coating machine, and run it at a speed of 60m / min;
[0065] 4. Spraying: The sprayer gate is opened, and the atomized slurry is sprayed onto the surface of the base film;
[0066] 5. Drying: The coating film is dried in an oven;
[0067] 6. Rewinding: Use the rewinding mechanism to receive the dried coating film onto the reel core to obtain the finished coating film.
[0068] Example 3
[0069] A method for preparing a coated diaphragm for a lithium ion battery comprises the following steps:
[0070] 1. Slurry preparation: Prepare the PVDF spray slurry prepared in Example 3, the solid content of the slurry is 15%;
[0071] 2. Feeding: The slurry circulates on the machine, passes through a nozzle with a diameter of 1.3 mm, and is dispersed and atomized under a turntable with a diameter of 100 mm and 360 teeth. The feed flow rate is 4000 ml / min and the turntable speed is 8000 RPM.
[0072] 3. Unwinding: Load the base film onto the coating machine, start the coating machine, and run it at a speed of 60m / min;
[0073] 4. Spraying: The sprayer gate is opened, and the atomized slurry is sprayed onto the surface of the base film;
[0074] 5. Drying: The coating film is dried in an oven;
[0075] 6. Rewinding: Use the rewinding mechanism to receive the dried coating film onto the reel core to obtain the finished coating film.
[0076] Example 4
[0077] A method for preparing a coated diaphragm for a lithium ion battery comprises the following steps:
[0078] 1. Slurry preparation: Prepare the PVDF spray slurry prepared in Example 1, with a slurry solid content of 15%;
[0079] 2. Feeding: The slurry is circulated on the machine, passes through a nozzle with a diameter of 1.3 mm, and is dispersed and atomized under a turntable with a diameter of 100 mm and 360 teeth. The feed flow rate is 4000 ml / min and the turntable speed is 10000 RPM.
[0080] 3. Unwinding: Load the base film onto the coating machine, start the coating machine, and run it at a speed of 60m / min;
[0081] 4. Spraying: The sprayer gate is opened, and the atomized slurry is sprayed onto the surface of the base film;
[0082] 5. Drying: The coating film is dried in an oven;
[0083] 6. Rewinding: Use the rewinding mechanism to receive the dried coating film onto the reel core to obtain the finished coating film.
[0084] Example 5
[0085] A method for preparing a coated diaphragm for a lithium ion battery comprises the following steps:
[0086] 1. Slurry preparation: Prepare the PVDF spray slurry prepared in Example 2, the solid content of the slurry is 13%;
[0087] 2. Feeding: The slurry is circulated on the machine, passes through a nozzle with a diameter of 1.3 mm, and is dispersed and atomized under a turntable with a diameter of 100 mm and 360 teeth. The feed flow rate is 4000 ml / min and the turntable speed is 10000 RPM.
[0088] 3. Unwinding: Load the base film onto the coating machine, start the coating machine, and run it at a speed of 100m / min;
[0089] 4. Spraying: The sprayer gate is opened, and the atomized slurry is sprayed onto the surface of the base film;
[0090] 5. Drying: The coating film is dried in an oven;
[0091] 6. Rewinding: Use the rewinding mechanism to receive the dried coating film onto the reel core to obtain the finished coating film.
[0092] Comparative Example 1
[0093] A method for preparing a coated diaphragm for a lithium ion battery comprises the following steps:
[0094] 1. Slurry preparation: PVDF spraying slurry is common slurry FR903, and the solid content of slurry is 15%;
[0095] 2. Feeding: The slurry circulates on the machine, passes through a nozzle with a diameter of 1.3 mm, and is dispersed and atomized under a turntable with a diameter of 100 mm and 360 teeth. The feed flow rate is 2000 ml / min and the turntable speed is 3000 RPM.
[0096] 3. Unwinding: Load the base film onto the coating machine, start the coating machine, and run it at a speed of 100m / min;
[0097] 4. Spraying: The sprayer gate is opened, and the atomized slurry is sprayed onto the surface of the base film;
[0098] 5. Drying: The coating film is dried in an oven;
[0099] 6. Rewinding: Use the rewinding mechanism to receive the dried coating film onto the reel core to obtain the finished coating film.
[0100] Performance Testing:
[0101] The coated diaphragms obtained in Examples 1-5 and Comparative Example 1 were tested, and the specific test methods are as follows:
[0102] 1. Surface density test: The weighing method equipment for surface density measurement provided by Mettler Toledo was used to test the surface density of lithium battery separators in accordance with the ASTM D792-13 international standard.
[0103] 2. Energy density refers to the energy contained in a unit volume. The test is usually carried out on a workstation, using a charge and discharge test device to record the charge and discharge curves of the battery. Through these curves, the voltage changes of the battery under different charge and discharge conditions can be analyzed, and then the energy density can be calculated. The calculation formula is energy density = specific capacity × voltage.
[0104] 3. Assemble the diaphragm coated with PVDF slurry into a battery and perform an initial cycle test. Use a cycle tester to set the appropriate current density and voltage range. Cycle tests are usually performed at a current density of 0.5C to 3C to simulate the charge and discharge conditions in actual use.
[0105] Fourth, the electrochemical test method indirectly evaluates the porosity by measuring the conductivity of the separator in the electrolyte. Diaphragms with higher porosity generally have higher ionic conductivity and can therefore be evaluated by electrochemical impedance spectroscopy (EIS) technology.
[0106] Table 1 Test results
[0107]
[0108]
[0109] As can be seen from Table 1, the coated diaphragms prepared in Examples 1-5 of the present invention can effectively control the coating surface density, glue point size and glue point height by adjusting parameters such as slurry solid content, coating speed, nozzle diameter, turntable speed, flow rate, etc., and then improve the overall hardness of the battery cell according to the design requirements of the battery cell, facilitate the battery cell into the shell, increase the battery energy density, and increase the battery cycle life.
[0110] The above is only an exemplary embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a coated separator for a lithium ion battery, characterized in that: The following steps are involved: (1) Slurry preparation: PVDF spray slurry preparation, the slurry solid content is 6-15%; (2) Feeding: The slurry is circulated on the machine, passes through a nozzle with a diameter of 0.8-1.5 mm, and is dispersed and atomized under a turntable with a diameter of 110 mm and 360 teeth. The feed flow rate is 3000-5000 mL / min and the turntable speed is 5000-10000 rpm; (3) Unwinding: Load the base film onto the coating machine, start the coating machine, and operate it at a coating speed of 60-150 m / min; (4) Spraying: The sprayer gate is opened and the atomized slurry is sprayed onto the surface of the base film; (5) Drying: The coated film is dried in an oven; (6) Winding: Use a winding mechanism to roll the dried coating film onto a winding core to obtain a finished coating film.
2. The method for preparing a coated separator for a lithium ion battery according to claim 1, characterized in that: In step (1), the PVDF spray slurry includes the following raw materials by mass: 300-600 parts of deionized water, 0.04-0.25 parts of pH buffer regulator, 85-99.5 parts of vinylidene fluoride monomer, 0.5-15 parts of comonomer, 0.5-3 parts of sodium carboxymethyl cellulose, 0.2-6 parts of nano-hydroxyapatite powder, 0.3-3 parts of metallocene synergist, 0.2-1.0 parts of initiator and 0.08-0.35 parts of dispersant.
3. The method for preparing a coated separator for a lithium ion battery according to claim 2, characterized in that: The dispersant is one or more of polypropylene ammonium salt, fatty acid polyethylene glycol ester, guar gum, and fatty acid polyethylene glycol ester.
4. The method for preparing a coated separator for a lithium ion battery according to claim 2, characterized in that: The initiator is one or more of benzoyl peroxide, tert-butyl peroxide, dialkyl peroxide and dihydrogen peroxide.
5. The method for preparing a coated separator for a lithium ion battery according to claim 2, characterized in that: The preparation method of PVDF spray slurry comprises the following steps: S1: Mix deionized water, pH buffer regulator, vinylidene fluoride monomer, comonomer and sodium carboxymethyl cellulose under a pressure of 5.5-8.0 MPa and a temperature of 40-65° C. to obtain a mixture A; S2: adding nano-hydroxyapatite powder and metallocene enhancer to mixture A, mixing and stirring uniformly to obtain mixture B; S3: adding an initiator and a dispersant to the mixture B, mixing, stirring and dispersing, and preparing a PVDF spray slurry.
6. The method for preparing a coated separator for a lithium ion battery according to claim 1, characterized in that: In step (4), the base film comprises a commercial PP single-layer film, a PE single-layer film or a PP and PE multi-layer composite base film.
7. The method for preparing a coated separator for a lithium ion battery according to claim 1, characterized in that: In step (5), the drying temperature is 45-60°C.
8. A coated separator for a lithium ion battery, characterized in that: The method for preparing a coated diaphragm for a lithium ion battery according to any one of claims 1 to 7 is obtained.
9. Use of the coated separator for lithium ion batteries as claimed in claim 8 in lithium ion batteries.